(untitled) (Research, Society and Development, 2022)
The state of Alagoas has a history of high crime rates and social inequality, and its capital, Maceió, is considered one of the most violent areas in the world and with the presence of important socio-spatial differences, with aspects of gentrification, demonstrating marked inequality, social exclusion, poverty and segregation. Thus, this study aimed to identify and describe the epidemiological profile of deaths from external causes in the state of Alagoas, between the years 2010 and 2020. This is a retrospective, analytical, observational, and cross-sectional study, of quantitative approach, based on data submitted to the Mortality Information System (SIM), and made available through the Department of Informatics of the Unified Health System (DATASUS). The variables collected were: number of deaths from external causes, distribution by sex, age group, main diseases, and incidence by health region. In the state of Alagoas, from 2010 to 2020, 34,308 deaths from external causes were confirmed, with males being the most affected with 2,9988 records (87.43%). There is a high incidence of deaths in males due to the greater susceptibility of young men to economic and social circumstances than other demographic groups regarding the factors that influence the risk of homicide. Therefore, the results presented are necessary to help subsidize health and safety policies in the state of Alagoas, minimizing the occurrence of deaths from preventable causes, such as mortality from external causes.